Dissociable Effects of Subthalamic Stimulation in Obsessive Compulsive Disorder on Risky Reward and Loss Prospects. (1st July 2018) - Voon, Valerie; Droux, Fabien; Chabardes, Stephan; Bougerol, Thierry; Kohl, Sina; David, Olivier; Krack, Paul; Polosan, Mircea
Highlights: The STN mediates dissociable valence prospects on risk seeking in OCD. DBS targeting the associative-limbic STN decreases risk taking to reward prospects. Acute DBS shows an impaired sensitivity to magnitude during loss anticipation. Abstract: Our daily decisions involve an element of risk, a behavioral process that is potentially modifiable. Here we assess the role of the associative-limbic subthalamic nucleus (STN) in obsessive compulsive disorder (OCD) testing on and off deep-brain stimulation (DBS) on anticipatory risk taking to obtain rewards and avoid losses. We assessed 12 OCD STN DBS in a randomized double-blind within-subject cross-over design. STN DBS decreased risk taking to rewards ( p  = 0.02) and greater risk taking to rewards was positively correlated with OCD severity ( p  = 0.01) and disease duration ( p  = 0.01). STN DBS was also associated with impaired subjective discrimination of loss magnitude ( p  < 0.05), an effect mediated by acute DBS rather than chronic DBS. We highlight a role for the STN in mediating dissociable valence prospects on risk seeking. STN stimulation decreases risk taking to rewards and impairs discrimination of loss magnitude. These findings may have implications for behavioral symptoms related to STN DBS and the potential for STN DBS for the treatment of psychiatric disorders.